Seascape ecology in the vicinity of a Blake Ridge cold seep - Johnson, Kellie; Taylor, Avery; Socha, Annika; Barkyoumb, Ellie; Nakamura, Koichi; Kaiser, Carl L.; German, Christopher R.; Yoerger, Dana R.; Van Dover, Cindy Lee (Frontiers in Marine Science, 2023)
Systematic surveys of the distribution of epibenthic megafaunal species relative to one another and to environmental variables in the deep sea can lead to inferences and testable hypotheses regarding factors that influence their distributions. Here we use a seascape approach to provide insight into the character and spatial extent of the influence of a chemosynthetic seep on the distribution of epibenthic megafauna and the nature of transition zones (ecotones). Faunal distributions were determined from georeferenced images of the seabed collected during a systematic survey (~ 400 m x 400 m) by the Autonomous Underwater Vehicle Sentry in the vicinity of a newly discovered methane bubble plume on the Blake Ridge Diapir. The survey area was found to include both seep and non-seep habitats. The sphere of influence of seep productivity on the surrounding benthic megafaunal assemblage was limited—on the order of 10’s of meters—based on ecotone analysis. Small but detectable redox anomalies in the water column (5 m above bottom) in the study area occurred on a similar horizontal scale. Distributions of background megafaunal taxa were non-random for many morphotypes and included both positive and negative associations between morphotypes and the seep habitat. Subtle variations in depth (<6 m) correlated with distributions of seep-associated vesicomyid clams, which occupy shallow depressions in the seabed. The seep habitat itself, comprising a patchy mosaic of megafaunal sub-communities (e.g., clam bed, mussel bed, background soft-sediment bathyal taxa) and transition zones, was at least as diverse as the surrounding non-seep habitat and contributes seep endemic morphotypes to regional biodiversity. While seep productivity may support prey fields for deep-diving beaked whales, any relationship between the seeps and whale feeding areas remains intriguing speculation. Like many other regions of the deep sea, Blake Ridge South has accumulated marine litter, including litter likely originating from scientific endeavors. The suite of observations and analyses deployed here underscore the importance of seep habitats in enriching regional biodiversity, provide a glimpse of the non-random complexity of species distributions from a seascape perspective, and establish ecological baselines against which future studies may measure natural and anthropogenic changes in the seascape.